Mariana and Brumadinho: graphic essay (Palíndromo, 2022)
It is a set of visual representations in print engraving, in woodcut, specifically, built from the feelings experienced during a visit to Paracatu de Baixo, District of the city of Mariana, Minas Gerais, in 2017, two years after the same having been hit by an iron mining dam mud spill. As part of the visit, an art workshop was held with inhabitants of the region, at the invitation of the UFOP Ouro Preto Winter Festival - Mariana campus. To the set of woodcuts on Mariana, a few more were added in 2019, engraved after another spill, this time in the city of Brumadinho, also in Minas Gerais, decimating hundreds of people. The engravings in this graphic essay were built by observation, memory, imagination, intuition about images conveyed by the media of the Brumadinho tragedy and by the artist’s own visual poetics. They are attempts at visual artistic expression of the events that took place, in homage to the people who died in the two mud spills and in solidarity with the residents affected by the dams.
Keywords: Engraving; Print; Struck by dams; Artistic Visual Poetics